Q: What is Xy divided by y squared?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

x(y - 1)(y + 1)

x+y

It is x^2 + xy + y^2

The answer? There is no "answer" There cannot be an answer because they are all different. In order to make calculations, the variables have to be the same. x squared, xy, y squared are the variables, and none of them match. Therefore your "answer" must look like this: 9x squared - 6xy + y squared - 81. Hope I Helped :D

(1/x) - (1/y) = (1/z) Get the left-hand side over a common denominator:- (y-x)/xy = 1/z Take the reciprocal of both sides:- z = xy / (y-x)

Related questions

The GCF is xy

The only common factor to all terms is yz. → xy³z² + y²z + xyz = yz(xy²z + y + x)

x(y - 1)(y + 1)

4

x+y

x=y+3t Original formula: y2 -xy = 9t2 -3xt (assumes you meant "9 times t2 " and not (9t)2 ) y2 = xy +9t2 -3xt y2 - 9t2 = xy - 3xt (y-3t)(y+3t) = x(y-3t) (y-3t) = x

y/y2 = 1/y

Divide by 'x'; x2+xy/x = x(x+y)

It is x^2 + xy + y^2

x2y + axy + abx + a2b Factor by grouping. xy(x + a) + ab(x + a) (xy + ab)(x + a)

(x2 - y2)/(x - y) = (x + y)(x - y)/(x - y) = x + y

y=f(x)= x(2x+y)=7 f(x)=2x^2 +xy -7 = 0 y=2x^2 +xy -7 y-xy -7 + 2x^2 = 0 y(1-x)=2x^2-7 y=(2x^2-7) / (1-x) Excuse the working. Y equals 2 X squared minus 7 all divided by 1-X